Sensitivity of Campylobacter jejuni Virulence genes flaA,mapA and hipO by Polymerase chain reaction - Marimuthu, Dhanalakshmi; Sekar, Muthu; L, Gunasaleen; Vivekanandan, Bhanurekha; Singaram, Balakrishnan; Raj, Gopal Dhinakar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Campylobacter jejuni is more frequently associated with zoonotic bacterial cause of foodborne gastroenteritis in humans. Effective diagnosis of C. jejuni infection in various matrix like foods of animal origin, environment  and human is crucial to maintain public health.  Since molecular diagnosis of C. jejuni carries several advantages over conventional microbial culture techniques, in this study, the limit of detection for the selected virulence genes of C. jejuni (flaA,mapA and hipO) were evaluated to know the suitability of them to be used as molecular diagnostic targets for early detection of C. jejuni by  in- house designed primers  by conventional PCR. Analytical sensitivity of these genes were assessed in terms of  Colony Forming Units (103 CFU/ ml, 102 CFU/ ml, 101 CFU/ ml, 100 CFU/ ml) and DNA concentration (100 ng,10 ng, 1 ng, 100 pg, 10 pg and 1 pg ) of C jejuni  cultures. Results revealed  that the primers targeting flaA have superior limit of detection as 10CFU  and 1pg of C. jejuni DNA. Whereas  mapA and  hipO have 10 CFU; 10 pg DNA and  100 CFU ;10 ng DNA detection limit respectively. Gene mapA  had comparable detection limits in terms of CFU with flaA but found to be less  sensitive  with respect to DNA concentration but hipO has 102 fold lesser limit of  detection.
Keywords: C.jejuni; flaA; PCR; Analytical sensitivity